2005
DOI: 10.1038/sj.ejcn.1602167
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and possible pitfalls of a preventive Polypill: confessions of a health promotion convert

Abstract: A proposal by Wald and Law (2003) for a single pill containing a statin, three half-dose antihypertensives, aspirin, and folic acid, met with a storm of controversy and seemed to have been relegated as much to the fanciful as to the accolades it might have deserved. The benefits such a Polypill could confer on people age 55 þ y were to reduce both cardiovascular and stroke events by 80% or more. Considering the daunting and, at best, slow process of changing the same risk factors through health promotion inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Green) wrote a thoughtful article in which he speculated that part of professionals' response to the polypill strategy would be resistance because of a concern that it might detract from the lifestyle changes (e.g. eating a healthy diet) that people should undertake to promote good health [11]. Green asserted that early primary prevention (e.g.…”
Section: The Debate Beginsmentioning
confidence: 96%
See 1 more Smart Citation
“…Green) wrote a thoughtful article in which he speculated that part of professionals' response to the polypill strategy would be resistance because of a concern that it might detract from the lifestyle changes (e.g. eating a healthy diet) that people should undertake to promote good health [11]. Green asserted that early primary prevention (e.g.…”
Section: The Debate Beginsmentioning
confidence: 96%
“…thoughtful consideration ensued, during which publications emerged highlighting not only the potential disadvantages, but the potentially large upsides surrounding the concept. Following thoughtful consideration, some physicians and other health professionals emerged as converts, and advocated for clinical trials to evaluate the effectiveness of the polypill [10,11]. We are now in the era of clinical trials.…”
Section: Era Of Clinical Trialsmentioning
confidence: 99%
“…Several formulation of Pollypill have been developed thereafter, and clinical trials were also initiated regardless of emerging controversy on Pollypill to an extent that few researchers suggested that Pollypill might be detrimental for modern medicine. 8 This article aims to present the current best evidences regarding the use of Pollypill in CVD by systematic review and meta-analysis of available clinical trials on Pollypills.…”
Section: Introductionmentioning
confidence: 99%